Biogenic synthesis of a Ag–graphene nanocomposite with efficient photocatalytic degradation, electrical conductivity and photoelectrochemical performance. (19th August 2015) - Khan, Mohammad Ehtisham; Khan, Mohammad Mansoob; Cho, Moo Hwan
Abstract : Visible light-driven photocatalytic degradation of organic pollutants using the Ag–graphene nanocomposite. Abstract : This paper reports an environmentally benign, simple, cost efficient, one-step, surfactant free, and biogenic synthesis of a silver–graphene (Ag–graphene) nanocomposite using an electrochemically active biofilm (EAB). The EAB was used for the reduction of Ag + to Ag 0 onto the graphene sheets. The morphology, structure, composition, and optical properties and contact angle of the Ag–graphene were obtained using a range of techniques which confirmed the anchoring/presence of silver nanoparticles (AgNPs) onto the graphene sheets. The photocatalytic activity of Ag–graphene was evaluated by the degradation of methylene blue and Congo red dye in aqueous solution at an ambient temperature in the dark and under visible-light irradiation. The results showed that the photocatalytic activity of the Ag–graphene nanocomposite was enhanced significantly by the loading of AgNPs in the graphene sheets. Contact angle measurements confirm the hydrophilic nature of the Ag–graphene nanocomposite which is very helpful in photocatalysis. The electrical conductivity and photocurrent measurements of the Ag–graphene nanocomposite exhibited a much better performance than P–graphene. This study highlights the design of a novel facile synthetic route for a new photocatalyst using the SPR of Ag and graphene as a support. The as-synthesized Ag–graphene nanocomposite has potential applications in photocatalytic degradation, photoelectrodes and optoelectronic devices.